Pillarization of double layer hydroxides using H3[-PW12O40]nH2O: effect of pillarization time - Muhammad Imron; Muhammad Said (Science and Technology Indonesia, 2017)
The pillarization of Mg/Al double layer hydroxides using polyoxometalate H3[α-PW12O40]·nH2O by comparing the pillarization time i.e. 3 hours, 6 hours, 9 hours, 12 hours, 24 hours, 36 hours and 48 hours has been done. The product of a pillarization was characterized using an FT-IR spectrophotometer and XRD analysis. The result characterization of FT-IR spectrophotometer does not show the optimum of pillarization each time condition. Characterization using XRD shows the optimum pillarization process at 36 hours by showing the existence of double layer hydroxides material at diffraction angle 11.69o deg, 18.30o deg and 34.71o deg. Diffraction in the 60o-63o deg indicates the existence of a pillarization double layer hydroxides. Keywords: Layered double hydroxides, pillarization, polyoxometalate H3[α-PW12O40]·nH2O.